ANALISIS STRATEGI BISNIS DALAM MENINGKATKAN KEPUASAN KONSUMEN PADA BISNIS REFLEXOLOGY GRIYA SEHAT DI HOWITZER RAYA - Hermawan , Rudianto; Rd. Kusyeni; Saifullah, Saifullah; Putri, Anis Taufina (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2025)
This research aims to analyses the right business strategy of Griya Sehat Reflexology Business on Howitzer Raya in an effort to increase customer satisfaction. SWOT analysis is used to identify internal strengths and weaknesses as well as external opportunities and threats faced by the company. This research uses a qualitative method with data collection through interviews and field observations. The results showed that Griya Sehat Reflexology Business has strong internal strengths, such as resources, technology, and organizational capabilities. However, the company also faces threats from competitive rivalry and buyer bargaining power. Based on SWOT analysis, an effective business strategy to increase customer satisfaction is the S-0 (Strength - Opportunity) strategy, which minimizes weaknesses and maximizes strengths and opportunities. Thus, this research hopes to contribute to businesses in increasing customer satisfaction and maintaining their competitive advantage. The results of this research are expected to be used as a reference for further research and contribute to the development of science.